2019
DOI: 10.33545/gynae.2019.v3.i6e.428
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spot urinary protein-creatinine ratio as a predictor of preeclampsia

Abstract: Background and Objectives: Hypertensive disorders are the most common medical complications of pregnancy with an incidence of 12-22% and are rampant globally. The aim of the study was to establish whether a spot urinary protein -creatinine ratio (UPCR) measured between 20-24 weeks of gestation can predict subsequent development of preeclampsia Methods: The prospective observational study included 120 pregnant mothers with singleton pregnancy with normal renal function having no proteinuria, attending antenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
3
1
Order By: Relevance
“…In the present study, 74 (75.5%) were found to be positive (+3) by urinary dipstick grading which is similar to a study given by Mahesh et al that reported 53 patients positive with urinary dipstick grading [ 18 ] whereas contrast with the above-mentioned studies Amin et al reported a very less number of positive (+3) patients 10 (9.8%) [ 23 ]. In the present study, the sensitivity of 85.71%, and specificity of 95.24% validates the spot UACR in the prediction of significant proteinuria which is similar to a study given by Mahesh et al and Modak et al that demonstrated sensitivity of 95% and 80%, respectively, and specificity of 80% and 94.06%, respectively [ 18 , 19 ]. In contrast with the above-mentioned studies, the study given by Amin et al reported high sensitivity of 89.7% with low specificity of 54.2% [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, 74 (75.5%) were found to be positive (+3) by urinary dipstick grading which is similar to a study given by Mahesh et al that reported 53 patients positive with urinary dipstick grading [ 18 ] whereas contrast with the above-mentioned studies Amin et al reported a very less number of positive (+3) patients 10 (9.8%) [ 23 ]. In the present study, the sensitivity of 85.71%, and specificity of 95.24% validates the spot UACR in the prediction of significant proteinuria which is similar to a study given by Mahesh et al and Modak et al that demonstrated sensitivity of 95% and 80%, respectively, and specificity of 80% and 94.06%, respectively [ 18 , 19 ]. In contrast with the above-mentioned studies, the study given by Amin et al reported high sensitivity of 89.7% with low specificity of 54.2% [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the mean SBP was found to be 150.12±8.95 and the mean DBP was found to be 101.20±6.12, which corresponds with a study given by Amin et al and Mahesh et al that demonstrated mean SBP of 152±18.2 range between 132-178 and 155.26±10.08, respectively, and mean DBP of 96.4±11.3 ranging between 78-116 and 102.11±7.04, respectively [ 18 , 23 ]. In contrast with the above study given by Modak et al, the mean SBP and DBP were 117.6 and 72.4, respectively [ 19 ]. In this study, the maximum number of patients were in the non-severe PE group 59 (60.2%) and the rest were in the severe PE 39 (39.8%).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…[11][12][13] There are studies that show strong association between random protein-creatinine ratio and 24 hour urinary protein excretion, the international society for the study of hypertension in pregnancy has accepted this test as a method for identifying significant proteinuria. 14 This suggests that microalbuminuria and elevated spot protein creatinine ratio in early pregnancy could predict preeclampsia.…”
Section: Introductionmentioning
confidence: 99%